Student Evaluations of Teaching Are Mostly Awfully Wrong - Noel Otu; Ntiense E. Otu (Universal Journal of Educational Research)
Student evaluations of teaching (SETs) have been used, researched, and debated for many decades. It is a common practice in higher education institutions, with the supposed purpose of improving course quality and effectiveness, but with unintended consequences of encouraging and motivating poor teaching and causing grade inflation. There is strong evidence that SET “effectiveness” does not measure teaching effectiveness. This paper reviews empirical research examining common concerns about the usefulness (positive and negative) and accuracy of SETs. The findings reveal that student satisfaction relates to their anticipated/expected grades in their courses; hence, they want to get good grades and their instructors want to get a good rating of SET, and this results in grade inflation. The key points are that SETs (1) allow students to speak their “mind”, (2) have no compelling correlation between quality of teaching and learning effectiveness, (3) reward easy, less demanding, and lazy teachers with a positive rating, (4) are biased against gender, attractiveness, ethnicity, race, etc., (5) are weaponized against “some” faculty members, and (6) are like asking convicts awaiting sentencing to evaluate the judge or jurors who convicted them.